2016
DOI: 10.1155/2016/2570237
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Dumping Syndrome after Sleeve Gastrectomy and Roux-en-Y Gastric Bypass: Early Results of a Multicentre Prospective Study

Abstract: Background. Bariatric surgery is an important field of surgery. An important complication of bariatric surgery is dumping syndrome (DS). Aims. To evaluate the incidence of DS in patients undergoing bariatric surgery. Methods. 541 patients included from 5 nutrition and bariatric centers in France underwent either LSG or LRYGB. They were evaluated at 1 month (M1) and 6 months (M6) postoperatively by an interview and completion of a dumping syndrome questionnaire. Results. 268 patients underwent LSG (Group A) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…Studies have shown that even patients undergoing sleeve gastrectomy can experience DS post‐operatively, although the number of patients who experience DS was lower in sleeve gastrectomy compared with RYGB surgery . This is interesting because the number of sleeve gastrectomies is increasing worldwide and it could be particularly relevant if we are to regard DS as the positive phenomenon that the patients considered DS to be.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that even patients undergoing sleeve gastrectomy can experience DS post‐operatively, although the number of patients who experience DS was lower in sleeve gastrectomy compared with RYGB surgery . This is interesting because the number of sleeve gastrectomies is increasing worldwide and it could be particularly relevant if we are to regard DS as the positive phenomenon that the patients considered DS to be.…”
Section: Discussionmentioning
confidence: 99%
“…The first‐line approach to the management of dumping syndrome is dietary modification which is effective mostly in patients with mild symptoms . Currently, there is no approved medical treatment available for patients with dumping syndrome .…”
Section: Introductionmentioning
confidence: 99%
“…One of the many complications of weight-reducing surgeries is dumping syndrome. The occurrence of dumping syndrome after bariatric surgery is more common in Laparoscopic Roux-en-Y gastric bypass than in laparoscopic sleeve gastrectomy [4].…”
Section: Discussionmentioning
confidence: 97%
“…It is characterized by changes in the fluid influx or the release of hormones. Symptoms of late dumping syndrome include feeling hungry, loss of consciousness, and sweating [4].…”
Section: Discussionmentioning
confidence: 99%